2006
DOI: 10.1079/phn2005866
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of undiagnosed diabetes among adult Moroccan Sahraoui women

Abstract: Objective: The goal of the present work was to examine the prevalence and associated risk factors of undiagnosed diabetes among urban Moroccan Sahraoui women. Design and setting: Randomised sample of adult women living in the city of Laayoune in south Morocco who visited public health centres during an immunisation campaign. Body weight, height, waist and hip circumferences, blood pressure, fasting plasma glucose (FPG), triglycerides, dietary intake and physical activity were collected. Subjects: Data were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
3
12
1
Order By: Relevance
“…In our findings, increasing fasting blood glucose was the major independent variable associated with hypertension. The overall prevalence of IFG in our study was lower than the Addis Ababa report (21.6%) and similar with that of a study done in Morocco, 5.5% [ 8 , 20 ]. Moreover, the computed prevalence of IFG differs significantly with areas of residence and age.…”
Section: Discussionsupporting
confidence: 89%
“…In our findings, increasing fasting blood glucose was the major independent variable associated with hypertension. The overall prevalence of IFG in our study was lower than the Addis Ababa report (21.6%) and similar with that of a study done in Morocco, 5.5% [ 8 , 20 ]. Moreover, the computed prevalence of IFG differs significantly with areas of residence and age.…”
Section: Discussionsupporting
confidence: 89%
“…Of the 12,825 citations retrieved from the six databases, 48 research reports were found eligible (Fig. 1); 46 reported T2DM prevalence [45–90] while 24 reported pre-DM prevalence [48, 49, 51–57, 60, 62, 63, 66, 67, 70, 73, 75, 81, 85, 88–90].…”
Section: Resultsmentioning
confidence: 99%
“…Unclear pregnancy statusAll20–49 yearsDM defined as FPG ≥ 7.0 mmol/L, according to the WHO 2003 criteria29452127.220–29 years1246423.430–39 years857536.240–49 yeas84211713.9 Diejomaoh et al, 2007 [58]10/2002–06/2004KuwaitObstetrics department, Maternity HospitalCSConsecutivePatients who had ≥ 3 consecutive spontaneous miscarriages were classified as patients with recurrent spontaneous miscarriageAllThe fasting glucose was determined soon after the collection of the blood samples3500.0 Tohme et al, 2005 [59]2003–2004LebanonHousehold surveyCSSystematic samplingWomen recruited from general population with an unclear pregnancy statusAll30–50 yearsSelf-reported DM. Diagnosed by a health professional and on management of DM544397.230–40 years311165.141–50 years233239.9 Rguibi and Belahsen, 2005 [60]10/2001–04/2002Morocco, LaayounePublic Health Center during an immunization programCSRandom SamplingNon-pregnant women aged 15 years or older, Sahraoui ethnic origin with no previous systemic diseaseAll15–34.9 yearsAccording to the ADA criteria FPG was categorized into normal fasting glucose (NFG) (FPG,6.1 mmol/l), IFG (IFG) (FPG 6.1–6.9 mmol/ l) and diabetes (FPG > or equal 7 mmol/ l)11321.815–25 years4200.025–34.9 years7122.8 Gowri et al, 2011 [61]Unclear, Over a period of one calendar yearOman, MusactObstetrics Department of the Sultan Qaboos University HospitalCSConsecutivePregnant Omani women with a mean an age range of 24–42 years attending ANC care servicesAllBlood testing1261814.3 Al-Lawati et al, 2002 [62]First quarter of 2000OmanNation–wide surveyCS…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations